Genios breves - Nora Avaro (Cuadernos LIRICO, 2021)
For Michael Holroyd, John Aubrey's Brief Lives, collected and published posthumously in 1813, almost a hundred years after they were written, were "spontaneous impressions, arising more from his imaginative gifts than from laborious research", an attitude that did not in any way undermine them, but on the contrary, put them on the podium of the biographical precursor. In short lives, instant detail is more splendid than any documentary finding. Jorge Luis Borges, following Marcel Schwob, called it a "circumstantial invention". In what follows, under the cover of these and other brief geniuses such as Virginia Woolf and Lytton Strachey, we will read prologues and synthetic biographies of Borges, written throughout his life by commission.